Co-ideation of disaster preparedness strategies through a participatory design approach: Challenges and opportunities experienced at Turrialba volcano, Costa Rica - Van Manen, Saskia (2015)
Disaster preparedness is key to coping and adaptation during the immediate aftermath of a natural hazard, but the majority of those at risk do not feel prepared. In this participatory action research we investigate the use of a participatory design approach to increase disaster preparedness around Turrialba volcano, Costa Rica. We present a case study of two ideation workshops and explore the process, outcomes, challenges and opportunities during ideation. Socio-cognitive dimensions, specifically risk and responsibility transfer, appear to be important factors influencing the uptake of self-protective measures. Challenges in workshop facilitation were of a human, cultural and resource nature. However, the overall process was successful with participants showing indications of empowerment and a number of pressing design opportunities identified.